PENGARUH SHOPPING LIFESTYLE, FASHION INVOLVEMENT DAN POSITIVE EMOTION TERHADAP IMPULSE BUYING BEHAVIOR - Imbayani, I Gusti Ayu; Novarini, Ni Nyoman Ari (Jurnal Ilmiah Manajemen & Bisnis, 2018)
The Influence of Shopping Lifestyle, Fashion Involvement and Positive Emotion on Impulse Buying Behavior. In making purchases, consumers prefer modern shopping to traditional shopping places. It is often done unplanned. Currently, type of modern shopping spot that is popular is lifestyle shopping center. Increased lifestyle shopping center in Badung regency from year to year makes business opportunities for business people, especially in fashion field. Shopping lifestyle reflects a person's choice of spending time and money. With the availability of time, consumers will have plenty of time to shop. And with their money, they will have a high purchasing power. Fashion involvement refers to one's involvement in a fashion product that is driven by the need and interest in the product. Impulse buying experienced by consumers can be influenced by positive emotion. This research was conducted to find out the influence of shopping lifestyle, fashion involvement and positive emotion toward impulse buying behavior. There were 220 respondents. The sampling method was purposive sampling method. The analysis technique used in this research is Multiple Linear Regression Analysis. The results with multiple linear regression analysis showed that shopping lifestyle, fashion involvement and positive emotion had a significant positive effect on the impulse buying behavior. Keywords: fashion involvement, impulse buying, positive emotion, and shopping lifestyle.